A avaliação da aprendizagem nos anos iniciais do ensino fundamental da escola Dr. Vicente Maués em Abaetetuba-PA - RIBEIRO, Luciana Helena Gomes (2019)
The evaluation of the precise learning is linked in a continuous and procedural way to the school daily, with the intention to improve the process of teaching / learning, promoting permanent reflections that help to reach the objectives of the teacher and the student in the construction of knowledge. For this, there are numerous evaluation instruments that can be used to assist the teacher in achieving the proposed objectives, providing a formative evaluation. The present work aims to understand the evaluation practices present in a class of 3rd year of elementary school; to analyze the conceptions of evaluation comprising its dimension and its implications in the evaluation practice; observe the evaluation practices; to investigate the evaluation tools present in the daily classroom of a public elementary school; For the purposes of analysis, a qualitative investigation was chosen, since it is understood that this is the most adequate way to achieve the proposed objectives. Initially a bibliographical research was carried out, explaining the conceptions of several authors that discuss on the subject evaluation, through books, scientific articles and periodicals. Data collection was carried out at a public school located in the city of Abaetetuba-Pará, together with the students and teacher of the 3rd year of elementary school, using observations and questionnaire as data collection instruments. Evaluation should not be a final product, but should be diagnostic, with the intention of always verifying what the student already knows, making it possible to trace objectives, reflecting which evaluation instruments can be used to achieve those objectives, and also of an evaluation that is a formative, procedural, continuous, that aims at accompanying the student always making this association between diagnostic evaluation and formative evaluation in order to make the student learn, verify the reason that the student is not able to learn.